Investigation of Infants with Hydrocephalus at Muhimbili National Hospital Using Anterior Transfontanelle Ultrasound Scan (Tanzania Medical Journal, 2017)
Background: Hydrocephalus is accumulation of cerebrospinal fluid in the cranium due to an imbalance between its production and absorption. There is an estimated 750,000 children and adults living with hydrocephalus. It is one of the most common developmental disabilities as it affects one in every 500 live births. There is a significant burden of hydrocephalus in East Africa, with more than 6000 new cases estimated per year and in the majority the cause is neonatal infection. Though there a number of studies on this study area, less is reported on the sonographic pattern of infantile hydrocephalus at our set-up. Objective: We aimed at determining the sonographic pattern of infantile hydrocephalus and the associated factors.Methods: Eighty (80) infants with hydrocephalus were consecutively included into the study. To every infant a cranial ultrasound was performed using an Ultrasound machine (Phillips, HP5000, Eindhoven, Best, Netherlands) with 2-5MHZ frequency curve-linear transducer. Questionnaires were used to collect demographic data and clinical information. Data analysis was done using the Statistical Package for Social Sciences (SPSS) version 17. Chi-square (X2) and Fisher’s exact tests were used to compare between clinical and sonographic variables. The p-value of < 0.05 indicated statistically significance differenceResults: Among the 80 studied infants 42 (52.5%) were males, the youngest was 1 month and the oldest was to 10 months old with mean age of 3.4 months. Hydrocephalus was most common (46.2%) in much younger infants aged 2 months and below (P-value=0.012). Non-communicating hydrocephalus was the most common type 62 (77.5%). Higher proportions of hydrocephalus were seen in infants with >2500grams of birth weight (76.2%), normal (spontaneous vertex) delivery 61 (76.2%) and those who were born at term (75%).Conclusion: Cranial Ultrasonography is an important tool in evaluation of infants with hydrocephalus. This information is helpful in making accurate management decision. Hydrocephalus was most common in much younger infants aged 2 months and below and the most common type was non-communicating hydrocephalus which accounted for 77.5%. Hydrocephalus is common in males and is associated with >2500grams of birth weight, term delivery and normal spontaneous vertex delivery though the observations were not statistically significant.